Braincase and endocranial anatomy of two thalattosuchian crocodylomorphs and their relevance in understanding their adaptations to the marine environment - Herrera, Laura Yanina (2018)
Thalattosuchians are a group of Mesozoic crocodylomorphs known from aquatic deposits of the Early Jurassic-Early Cretaceous that comprises two main lineages of almost exclusively marine forms, Teleosauridae and Metriorhynchoidea. Teleosaurids were found in shallow marine, brackish and freshwater deposits, and have been characterized as semiaquatic near-shore forms, whereas metriorhynchids are a lineage of fully pelagic forms, supported by a large set of morphological characters of the skull and postcranial anatomy. Recent contributions on Thalattosuchia have been focused on the study of the endocranial anatomy. This newly available information provides novel evidence to suggest adaptations on the neuroanatomy, senses organs, vasculature, and behavioral evolution of these crocodylomorphs. However, is still not clear if the major morphological differences between teleosaurids and metriorhynchids were also mirrored by changes in the braincase and endocranial anatomy. Based on X-ray CT scanning and digital endocast reconstructions we describe the braincase and endocranial anatomy of two well-preserved specimens of Thalattosuchia, the semiaquatic teleosaurid Steneosaurus bollensis and the pelagic metriorhynchid Cricosaurus araucanensis. We propose that some morphological traits, such as: an enlarged foramen for the internal carotid artery, a carotid foramen ventral to the occipital condyle, a single CN XII foramen, absence of brain flexures, well-developed cephalic vascular system, lack ofsubtympanic foramina and the reduction of the paratympanic sinus system, are distinctive features of Thalattosuchia. It has been previously suggested that the enlarged foramen for the internal carotid artery, the absence of brain flexures, and the hypertrophied cephalic vascular system were synapomorphies of Metriorhynchidae; however, new information revealed that all of these features were already established at the base of Thalattosuchia and might have been exapted later on their evolutionary history. Also, we recognized some differences within Thalattosuchia that previously have not been received attention or even were overlooked (e.g., circular/bilobate trigeminal foramen, single/double CN XII foramen, separation of the cranioquadrate canal from the external otic aperture